Post-embrionic development of the digestive tube of Dermatobia hominis (Linnaeus) (Diptera, Cuterebridae) - Vieira, Ana Maria [UNESP]; Lello, Edy de [UNESP] (Sociedade Brasileira de Zoologia, 1996)
The digestive tube of 2nd and 3rd instar larvae, pupae and newly emerged adults of Dermatobia hominis (Linnaeus, 1781) was studied anatomically. The specimens were dissected in buffer saline under a stereomicroscope, and the digestive tubes were placed on slides and fixed in 10% buffered formalin. Each tube was measured using a micrometric eye piece, and drawings were made with camera lucida. The results showed that the midgut, the hindgut and the Malpighian tubules with their ducts grow gradually during the larval development. The oesophagus and the salivary glands with their ducts grow only during the moult from the 2nd to the 3rd instar. In the pupal period, salivary glands grow gradually but disappeared after the 20th day. After metamorphosis the digestive tube regressed. This is expected since adult D. hominis lives about nine days without feeding. This fly, similar to other calyptratae muscoid flies shows no vestige of a crop during all post-embrionic development, and the adult has no salivary glands.
Keywords: Dermatobia hominis; digestive tube; anatomy; post-embrionic development